An Analysis of Educational Philosophy and the Values of the Pancasila Student Profile as the Foundation of the Kurikulum Merdeka - M. Agung Alwanda; Rizki Saputra (PT. Pusmedia Group Indonesia, 2025)
The transformation of Indonesia’s education system through the Kurikulum Merdeka reflects a paradigm shift from outcome-oriented learning to student-centered education. However, its implementation often focuses on technical aspects while neglecting philosophical and ideological foundations. This study aims to analyze the role of educational philosophy and the values of the Pancasila Student Profile as the foundation for the development of the Independent Curriculum. This research employs a Systematic Literature Review (SLR) method with a qualitative descriptive approach. Secondary data were collected from 17 national journal articles indexed in SINTA, published between 2022 and 2025, which discuss educational philosophy, Pancasila values, and the Kurikulum Merdeka. The analysis followed the PRISMA 2020 framework, consisting of four stages: identification (784 articles), screening (120 articles), eligibility assessment (45 articles), and inclusion (17 articles). The data were analyzed thematically based on the three dimensions of educational philosophy: ontology, epistemology, and axiology. The results reveal that educational philosophy serves as the conceptual and ideological foundation of the Kurikulum Merdeka, while the Pancasila Student Profile values provide ethical and moral guidance. The ontological dimension views humans as moral and cultural beings; the epistemological dimension emphasizes experiential and collaborative learning; and the axiological dimension focuses on the formation of character, ethics, and humanity. In conclusion, educational philosophy and the Pancasila Student Profile values are dialectically integrated within the Independent Curriculum, shaping a humanistic, reflective, and value-based education paradigm. This integration is essential for the success of national education implementation that is character-oriented and responsive to 21st-century challenges.